Local oestradiol administration – Vagifem®. Multicentre study - Markowska, Janina; Grabowski, Jacek P.; Olejek, Anita; Kozak-Darmas, Iwona; Baranowski, Włodzimierz; Polaszewski, Andrzej; Skrzypczak, Maciej; Fischer, Natalia; Mądry, Radosław; Tomaszewska, Kornelia; Muszyńska-Wiese, Ewa; Wawrzyniak, Anna (Menopause Review/Przegląd Menopauzalny, 2008)
137 women who underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy or in some cases received radiotherapy due to cervical and endometrial cancer were observed for local Vagifem ® (25 mg oestradiol) therapy evaluation. After 6 months of vaginal administration we noted a significant improvement of the symptoms: atrophic vaginitis, urinary incontinence, dysuric symptoms, bacterial infection as well as reported dyspareunia.